Influence of external factors on secondary embryogenesis and germination in somatic embryos from leaves of Quercus suber - Fernández-Guijarro, Bárbara; Celestino, Cristina; Toribio, Mariano (Plant Cell, Tissue and Organ Culture, 1995)
Somatic embryogenesis was obtained in cultures of leaves from young seedlings of Quercus suber L. A two- stage process, in which benzyladenine and naphthaleneacetic acid were added first at high and then at low concentrations, was required to initiate the process. Somatic embryos arose when the explants were subsequently placed on medium lacking plant growth regulators. The embryogenic lines remained productive, by means of secondary embryogenesis, on medium without growth regulators. However, this repetitive induction was influenced by the macronutrient composition of the culture medium. Both low total nitrogen content and high reduced nitrogen concentration decreased the percentage of somatic embryos that showed secondary embryogenesis. Our results suggest that alternate culture on medium that increases embryo proliferation and a low salt medium prohibiting embryo formation will partially synchronize embryo development. Chilling slightly reduced secondary embryogenesis but gave a modest increase in germination. Maturation under light followed by storage at 4 °C for at least 30 days gave the best results in switching embryos from an embryogenic pathway to a germinative one. Under these conditions 15% of embryos showed coordinated root and shoot growth and 35% formed either shoots or mostly roots. These percentages were higher than those of embryos matured in darkness. This result indicates that a specific treatment is required after maturation and before chilling to activate the switch from secondary embryo formation to germination.
Keywords: Cork oak; culture media; plant regeneration; recurrent embryogenesis; repetitive embryogenesis; Somatic embryogenesis

Influence of external factors on secondary embryogenesis and germination in somatic embryos from leaves of Quercus suber (Plant Cell, Tissue and Organ Culture, 1995)
Somatic embryogenesis was obtained in cultures of leaves from young seedlings of Quercus suber L. A two- stage process, in which benzyladenine and naphthaleneacetic acid were added first at high and then at low concentrations, was required to initiate the process. Somatic embryos arose when the explants were subsequently placed on medium lacking plant growth regulators. The embryogenic lines remained productive, by means of secondary embryogenesis, on medium without growth regulators. However, this repetitive induction was influenced by the macronutrient composition of the culture medium. Both low total nitrogen content and high reduced nitrogen concentration decreased the percentage of somatic embryos that showed secondary embryogenesis. Our results suggest that alternate culture on medium that increases embryo proliferation and a low salt medium prohibiting embryo formation will partially synchronize embryo development. Chilling slightly reduced secondary embryogenesis but gave a modest increase in germination. Maturation under light followed by storage at 4 °C for at least 30 days gave the best results in switching embryos from an embryogenic pathway to a germinative one. Under these conditions 15% of embryos showed coordinated root and shoot growth and 35% formed either shoots or mostly roots. These percentages were higher than those of embryos matured in darkness. This result indicates that a specific treatment is required after maturation and before chilling to activate the switch from secondary embryo formation to germination.